A study on issues of photovoltaic modules in solar energy system on safety, health and environmental aspect - Abdul Samad, Fadhilah Diyana; Awang, Mariah; Syazwan, M M Syafiq; A Rahman, M A; Musa, Mohd Kamaruzaman; Hamidon, Nuramidah; Rosli, Mohd Arif; Daud, Siti Zaleha; Ahmad, Faridahanim; Mohd Akhir, Mohd Shahrizan (2024)
Solar energy is one of the purest types of energy and is regarded as a green energy source. Solar energy benefits include reduced carbon emissions, no need for fossil fuels, long-term solar resources and shorter payback period. Solar energy, like other forms of energy, has various safety, health and environmental (SHE) issues. The research scope is limited to solar panel manufacturing companies and solar panel industries. The first objective is to address the SHE impact of solar energy technology, particularly PV modules, on human activity sustainability. The second objective is to suggest possible ways to reduce the effect of potential hazards of widespread use of PV modules. The third objective is to conduct a survey in order to determine the most feasible recommendation for mitigating the impact of the possible risk of widespread use of PV modules. The first and second objectives is met through the synthesis of theories and concepts through the literature review. For the third objective, a questionnaire survey was performed among Malaysia solar panel manufacturing sectors and solar panel companies, with 60 responses. Conjoint analysis is used to analyse the data gathered for the third objective. According to the result, respondents are exposed to various kinds of chemical compounds during manufacturing and decommissioning process. 85% of the respondents strongly agrees that all of the suggested recommendation are required to be executed as soon as possible. This analysis identifies potential environmental burdens. There are both negative and positive socioeconomic consequences. This article also recommended to conduct an interview with individuals involved in the manufacture and disposal of PV modules to obtain more accurate research findings and understand the genuine condition of employees. For future improvement, conducting a thorough examination of each recommendation that can be implemented in the current scenario in order to obtain a specific solution that reflects the current situation and specifies future research on employees in the PV module manufacturing and disposal industries are also suggested.